Factors associated with suicide in physicians: a silent stigma and public health problem that has not been studied in depth - Rátiva Hernández, Narda Katherine; Carrero-Barragán, Tania Yaritza; Ardila, Andrés Felipe; Rodríguez-Salazar, Juan Diego; Lozada-Martinez, Ivan David; Velez-Jaramillo, Elisa; Ortega Delgado, Daniel Aicardo; Fiorillo Moreno, Ornella; Navarro Quiroz, Elkin (Frontiers in Psychiatry, 2023)
Suicide is a complex and multifaceted public health issue that affects individuals from all walks of life, including healthcare professionals such as physicians. According to research, physicians have a higher risk of suicide compared to the general population, with an estimated suicide rate that is two to three times greater than that of the general population. Suicide in physicians can have devastating consequences, not only for the individual but also for their patients and colleagues. The factors contributing to suicide in physicians are numerous and often interrelated. Physicians are exposed to numerous stressors in their daily lives, including long work hours, high workload, burnout, and exposure to traumatic events. These stressors can lead to mental health problems such as depression, anxiety, and substance use disorders, which in turn can increase the risk of suicide. In addition to work-related stressors, personal factors such as relationship problems, financial stress, and a history of mental health problems can also contribute to suicide risk in physicians. Stigma and shame around seeking help for mental health issues may also prevent physicians from seeking treatment, exacerbating the problem. Understanding the complex factors that contribute to suicide in physicians is crucial for developing effective prevention strategies. For this reason, it is necessary to know the behavior of this phenomenon and the factors associated with a higher risk of suicide in this population. However, taking into account that different regions of the world vary in socioeconomic, cultural, professional, occupational, and health attributes, it is to be expected that the behavior of these risk factors will also be heterogeneous. At present, it is presumed that there is a significant gap in the evidence, due to a predominance of evidence on this topic from high-income countries. Considering the importance of having a comprehensive understanding of the risk factors for suicide in the medical population and possible strategies to mitigate this condition, the aim of this review is to analyze the most recent evidence on these factors, and to assess the quality of the evidence and gaps that need to be studied further